Changes in Cortical Sensitivity to Infant Facial Cues From Pregnancy to Motherhood Predict Mother–Infant Bonding. Issue 1 (4th December 2018) - Dudek, Joanna; Colasante, Tyler; Zuffianò, Antonio; Haley, David W.
Abstract : The transition to motherhood triggers changes in human brain structure that may facilitate mother–infant bonding. Although much research on maternal cortical responses to infant faces has focused on the postpartum period, no previous study has examined whether longitudinal functional changes in the maternal cortex during pregnancy and postpartum are associated with mother–infant bonding. Using electroencephalography, prenatal to postnatal changes in cortical sensitivity (P1, P2, late positive potential, N170 event‐related potentials) to infant and adult faces were examined in relation to reported mother–infant bonding in 40 mothers ( M age  = 30.5 years). Prenatal to postnatal increases in P1 and P2 responses to infant faces predicted stronger bonding. Findings suggest that cortical changes in attention allocation rather than in face‐specific encoding enhance bonding.